2011
DOI: 10.1093/ndt/gfr044
|View full text |Cite
|
Sign up to set email alerts
|

Iron overload as cardiovascular risk factor in children and adolescents with renal disease

Abstract: Children and adolescents with iron overload show more CVRFs, especially if they received replacement therapy with HD. Ferritin is related to CRP and IL-6 levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
6
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
6
6
1
Order By: Relevance
“…Similar findings have been found in transfusion-dependent anemias, such as sickle-b-thalassemia and myelodysplastic syndromes (33,34). A recent study, however, reported that IO can be a cardiovascular risk factor in children and adults on LTH (35).…”
Section: Discussionsupporting
confidence: 77%
“…Similar findings have been found in transfusion-dependent anemias, such as sickle-b-thalassemia and myelodysplastic syndromes (33,34). A recent study, however, reported that IO can be a cardiovascular risk factor in children and adults on LTH (35).…”
Section: Discussionsupporting
confidence: 77%
“…Due to confounding effects of the acute-phase response on the interpretation of most iron indicators, the assessment of iron status is challenging when concomitant inflammation is present. In fact, serum levels of ferritin were positively correlated with CRP, a measure of inflammation, in children and adults on HD [ 16 , 39 , 40 ]. Under minor inflammation, serum ferritin appears to be a most reliable biomarker of total body iron stores and ID is diagnosed below the cutoff serum ferritin levels of <15 ng/mL in individuals older than 5 years [ 1 ].…”
Section: Biomarkers Of Iron Status and Inflammation In Ckdmentioning
confidence: 99%
“…In support of this hypothesis, inflammation and hyperferritinemia (>500 ng/mL) were associated with cardiovascular and all-cause mortality in HD adults [ 90 ]. In addition, in dialysis children and adolescents with iron overload, ferritin levels showed a positive correlation with inflammation markers (CRP and IL-6) and left ventricular mass (LVM) [ 39 ].…”
Section: Ida In Ckdmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferritin as an acute-phase reactant is frequently elevated in CKD patients irrespective of their iron stores [49]. Increased serum ferritin levels are the result of systemic inflammation and correlate positively with the severity of inflammation [50,51]. Thus, the interpretation of serum ferritin is complicated by concomitant inflammation [35,45].…”
Section: Assessment Of Iron Statusmentioning
confidence: 99%